Assessment of knowledge, attitudes and practice among interns about over the counter drugs in a tertiary care hospital in India - Chatterjee, Sudipto; Vijendra, R.; Girish, K.; Koroth, Mahesh Kumar Manjeri (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Drugs that are dispensed against a valid prescription issued to a patient by a registered medical practitioner are known as “prescription-only drugs”. In India, they have been regulated under schedule H, H1, G, and X of the Drugs and Rules (1945). The drugs which are not included in the list of “prescription-only drugs” are considered to be over-the-counter drugs (OTC). There is no provision for an OTC drug schedule in the Drugs and Cosmetics Rules 1945, and these drugs have higher chances of misuse or abuse. This study was undertaken to assess the knowledge, attitudes and practice among medical interns about OTC drugs in a tertiary care hospital in India. Methods: This was a cross-sectional study, which was conducted at Kempegowda Institute of Medical Sciences and Research Center, Bangalore, Karnataka, India, from March 2018 to September 2018. A pre-validated questionnaire consisting of 24 questions to assess the knowledge, attitude, and practice was administered to 80 medical interns chosen by simple randomization, out of which 14 questions were related to knowledge, 6 related to attitude and 4 related to the practice. The participants were provided 30 minutes to complete the questionnaire. The data recorded were analyzed using Microsoft Excel. Results: There were some gaps in the knowledge, attitude and practice among the medical interns about OTC medications. Conclusions: There is a need for special emphasis on the MBBS curriculum about the use of OTC drugs.